(Ir)Rationality among Migrant Worker Families in Ponorogo: The Demolition of Joint Property after Divorce - Aini, Shofwatul; Hidayati, Niswatul (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
House demolition as a solution to joint property disputes appears to be an option for some Ponorogo migrant workers. In 2022, there were five cases of house demolitions in Ponorogo involving migrant families in Ponorogo. This study addresses three main issues: (1) the reasons why some migrant worker couples prefer to demolish joint-property houses; (2) how these reasons can be understood through Homans' theory of rational action; and (3) the socio-economic impacts of these actions. Data were collected through interviews and document analysis. This study argues that, first, the primary reason husbands and wives choose to demolish their house is due to feelings of disappointment and betrayal by their partners, coupled with fear that the house might later be used as a residence for their ex-partners and their new partners. Second, the act of demolishing the house is considered rational because the emotional harm caused by betrayal is perceived as equivalent to suffering an economic loss. Third, this demolition has socio-economic consequences for their children, who are unable to benefit from their parents' property. [Pembongkaran rumah sebagai solusi atas sengketa harta bersama tampaknya menjadi salah satu pilihan yang ditempuh oleh sebagian pekerja migran asal Ponorogo. Pada tahun 2022, tercatat lima kasus pembongkaran rumah di Ponorogo yang melibatkan keluarga pekerja migran. Penelitian ini mengkaji tiga persoalan utama, yaitu: (1) alasan pasangan pekerja migran memilih membongkar rumah yang merupakan harta bersama; (2) bagaimana alasan tersebut dapat dipahami melalui teori tindakan rasional Homans; dan (3) dampak sosial-ekonomi yang ditimbulkan dari tindakan tersebut. Data penelitian diperoleh melalui wawancara dan analisis dokumen. Penelitian ini berargumen bahwa, pertama, alasan utama suami dan istri memilih membongkar rumah adalah karena adanya perasaan kekecewaan dan pengkhianatan oleh pasangan, disertai kekhawatiran bahwa rumah tersebut kelak akan digunakan sebagai tempat tinggal oleh mantan pasangan bersama pasangan barunya. Kedua, tindakan pembongkaran rumah dipandang sebagai tindakan rasional karena kerugian emosional akibat pengkhianatan dimaknai setara dengan kerugian ekonomi. Ketiga, pembongkaran tersebut menimbulkan konsekuensi sosial-ekonomi, terutama bagi anak-anak, yang pada akhirnya tidak dapat menikmati atau memanfaatkan harta yang telah diusahakan oleh kedua orang tuanya selama masa perkawinan.]